Vitamin B-12 and cognition in the elderly. - Smith, A; Refsum, H (2009)
Vitamin B-12 deficiency is often associated with cognitive deficits. Here we review evidence that cognition in the elderly may also be adversely affected at concentrations of vitamin B-12 above the traditional cutoffs for deficiency. By using markers such as holotranscobalamin and methylmalonic acid, it has been found that cognition is associated with vitamin B-12 status across the normal range. Possible mediators of this relation include brain atrophy and white matter damage, both of which are associated with low vitamin B-12 status. Intervention trials have not been adequately designed to test whether these associations are causal. Pending the outcome of better trials, it is suggested that the elderly in particular should be encouraged to maintain a good, rather than just an adequate, vitamin B-12 status by dietary means.